2016
DOI: 10.1371/journal.pone.0164633
|View full text |Cite
|
Sign up to set email alerts
|

Incongruence between Verbal and Non-Verbal Information Enhances the Late Positive Potential

Abstract: Smooth social communication consists of both verbal and non-verbal information. However, when presented with incongruence between verbal information and nonverbal information, the relationship between an individual judging trustworthiness in those who present the verbal-nonverbal incongruence and the brain activities observed during judgment for trustworthiness are not clear. In the present study, we attempted to identify the impact of incongruencies between verbal information and facial expression on the valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…As we found an opposite pattern of activation, it is possible that our task could have evoked other neural processes than the ones underlying the priming effects reported by previous studies (Diéguez-Risco et al, 2013Morioka et al, 2016). For instance, Diéguez-Risco et al (2013 used happy-or anger-inducing sentences that might have worked as primes during the processing of FEE.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…As we found an opposite pattern of activation, it is possible that our task could have evoked other neural processes than the ones underlying the priming effects reported by previous studies (Diéguez-Risco et al, 2013Morioka et al, 2016). For instance, Diéguez-Risco et al (2013 used happy-or anger-inducing sentences that might have worked as primes during the processing of FEE.…”
Section: Discussionmentioning
confidence: 53%
“…The results obtained in the LPPs were consistent between the early and late time-windows, showing higher amplitudes in congruent than in incongruent trials. The direction of this effect is unexpected, since previous studies using context-target congruency tasks found larger LPPs after incongruent FEE, in conditions involving both implicit (Diéguez-Risco et al, 2013;Morioka et al, 2016) and explicit processing of congruency (Diéguez-Risco et al, 2015). Higher LPP amplitudes elicited by incongruent trials are systematically reported in the priming literature, namely in tasks requiring an evaluative congruity between primes and facial (Herring et al, 2011;Werheid, Alpay, Jentzsch, & Sommer, 2005) or verbal targets (Zhang, Li, Gold, & Jiang, 2010).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The facilitator' role in VT training needs to be emphasized. The communication incongruence, that is, when verbal and nonverbal information are inconsistent, diminishes trustworthiness (Morioka et al, 2016). Therefore, the facilitator needs to embody the validation methods and be empathic.…”
Section: Discussionmentioning
confidence: 99%
“…The P3 component registered in the same areas is being associated with operations on comparing the incoming information to the inner model of the stimulus and decision whether they are identical or not [42,43]. It is also supposed that the frontal areas of the cortex are connected with the operative memory mechanisms [44,45] and are responsible for evaluating the significance of verbal and non-verbal stimuli depending on the context and past experience [46,47]. The activation of those areas associated with verbal thinking (starting with analyzing letters and up to pronounce words mentally) was demonstrated, in particular, by fMRI [9,48].…”
Section: Discussionmentioning
confidence: 99%